Fenomena dan Terminasi Diapause Penggerek Batang Padi Putih (Scirpophaga innotata) - Solikhin Solikhin (Universitas Gadjah Mada, 1999)
Diapause of larvae of the white stem borers, Scirpophaga innotata (Walker), is interesting and can be terminated by exposing them in a certain low thermoperiod, so that the brain is activated to initiate the production of prothoracotropic hormone (PITH). In this case water is strongly suggested responsible for stabilizing this low thermoperiod by mechanism of buffering (capture and release) heat.